The Impact of Self Directed Learning and Digital Literacy for Study Result Pengelolaan Bisnis Ritel Subject Grade XI BDP SMK Negeri 1 Medan 2022/2023 - Rotua Angelita Marsaulina Silaen (MultiTech Publisher, 2023)
This research aims to find out the influence of Self Directed Learning and Digital Literacy on the Learning Results of Class XI BDP SMK Negeri 1 Medan. The population in this study is the entire student class XI BDP SMK State 1 Medan T.A 2022/2023 which totaled 66 students. The sampling technique was carried out using total samplings to obtain a sample of 66 students. In the meantime, for the collection of research data obtained from elevators and lists of student values. The result of the double linear regression test showed the constant value (a) of 4.019, the self-directed learning variable regression coefficient value of 0.623, then the Digital Literation variabel regression factor of 0.362. It was concluded that Self Directed Learning and Digital Literacy had a significant impact on Retail Business Management Lesson Results in Class XI BDP SMK State 1 Medan T.A 2022/2023.